2018
DOI: 10.1021/acsomega.8b01833
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Antiplasmodial Efficacy of β-Carboline Derivatives against Murine Malaria

Abstract: The difficulty of developing an efficient malaria vaccine along with increasing spread of multidrug resistant strain of Plasmodium falciparum to the available antimalarial drugs poses the need to discover safe and efficacious antimalarial drugs to control malaria. An alternative strategy is to synthesize compounds possessing structures similar to the active natural products or marketed drugs. Several biologically active natural products and drugs contain β-carboline moiety. In the present study, few selected β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…[ 69 ] The β‐carboline derivatives 29a , b exhibited 71.79% and 86.17% inhibition of P. berghei schizont maturation respectively at a concentration of 5 µg/ml, whereas the reference chloroquine exhibited 90.66% inhibition at 10 µg/ml. [ 70 ] These two hybrids did not cause any deaths and behavioral changes at a dose of >2.5 g/kg in the in vivo acute toxicity evaluation, suggesting their excellent safety profile. In the P. berghei ‐infected mouse model, compound 29a (50 mg/kg, orally) exhibited promising activity in terms of parasite clearance (suppression of 88.93% and 97.57% parasitemia at Days 5 and 28, respectively, while chloroquine group was 98.32% and 100% at a dose of 10 mg/kg) and enhancement of host survival (mean survival time: 23.4 days, while the untreated group was 8.2 days).…”
Section: Indole Hybridsmentioning
confidence: 97%
“…[ 69 ] The β‐carboline derivatives 29a , b exhibited 71.79% and 86.17% inhibition of P. berghei schizont maturation respectively at a concentration of 5 µg/ml, whereas the reference chloroquine exhibited 90.66% inhibition at 10 µg/ml. [ 70 ] These two hybrids did not cause any deaths and behavioral changes at a dose of >2.5 g/kg in the in vivo acute toxicity evaluation, suggesting their excellent safety profile. In the P. berghei ‐infected mouse model, compound 29a (50 mg/kg, orally) exhibited promising activity in terms of parasite clearance (suppression of 88.93% and 97.57% parasitemia at Days 5 and 28, respectively, while chloroquine group was 98.32% and 100% at a dose of 10 mg/kg) and enhancement of host survival (mean survival time: 23.4 days, while the untreated group was 8.2 days).…”
Section: Indole Hybridsmentioning
confidence: 97%
“…The acute toxicity studies of 9a (LD 50 > 4 g/kg) indicated its toxicological safety for oral administration at higher doses. 22 The compound was further evaluated for its antimalarial potential in vivo in monotherapy to confirm our previous findings, and lower doses were also tested to determine the median effective dose (ED 50 ) and its efficacy in combination therapy with artesunate. Rodent malaria parasite species are well-established experimental models for testing the efficacy of novel drug candidates.…”
Section: Resultsmentioning
confidence: 85%
“…The incorporation of aromatic substituents at the C1 position was reported to improve the activity, and the presence of the carbonyl group at the C3 position was also found to be important for the enhancement of activity [ 1 , 11 , 21 , 27 , 35 ]. Thus, we designed the preparation of the substituted THβCs via the efficient Pictet-Spengler reaction with tryptamine ( 1a ), L -tryptophan methyl ester ( 1b ), and appropriate aldehydes in acid media ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, THβC with an eight-carbon linear chain at the C1 position, (1 R ,3 S )-methyl 1-octyl-2,3,4,9-tetrahydro-1 H -pyrido[3,4- b ]indole-3-carboxylate, showed in vitro antifungal activity against Candida glabrata with disruption of the membranes of fungal cells by increased asymmetry and decomposition of the cell surface [ 20 ]. Thus, the pharmaceutically important β-carboline-based natural products are advantageous for medicinal and organic research, while 1,3 disubstituted THβCs are reported to be synthetically and biologically interesting analogs [ 35 ]. Currently, Tadalafil, the hydantoin fused at the nitrogen and C3 of THβC with a substituent at C1 is clinically used to treatment erectile dysfunction under the brand name Cialis [ 36 ] and is also used for pulmonary arterial hypertension treatment under the brand name Adcirca [ 37 ].…”
Section: Introductionmentioning
confidence: 99%